(3eaGJjM GdCUhds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
.. (3EPG Yde GdeLJgO HMce ef GdCMcGe GdTQYjI GdaQYjI HYO GSJaQGZ hSYg hHPd LgOg ajg adG ETcGd hdG THgI aj GYJHGQ Ydeg hchfg MLI TQYjI hLhGR GdGYJeGO Ydjg ShGA cGf Pdc GdYde YbdjG (B...s
(3BNQgG (B:s
... (3hZdHJg YOe MLjJg Xfhf bhjI cKjQI aj eQGQ cKjQI hdjSJ GdCOdI GdOGdI Ydi CUGdI eLjFg GdXf aj faS GdCMcGe TGedI deMd GdHMK HhLg ef GdhLhg (B. (3Je GdcJGHs
(3JHUQI GdYfhGf (B:s
(3YOe MLjI GdXfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 543s
(3GdPQjYI (B21\ 5173s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs